Service Value Broker Patterns: An Empirical Collection and Analysis - Yucong Duan; Keman Huang; Dan Chen; Yongzhi Wang; Ajay Kattepur; Wencai Du (International Journal of Networked and Distributed Computing (IJNDC), 2014)
The service value broker(SVB) pattern integrates business modeling, knowledge management and economic anal- ysis with relieved complexity, enhanced reusability and effi- ciency,etc. The study of SVB is an emerging interdisciplinary subject which will help to promote the reuse of knowledge, strategy and experience in service based designs and solutions. In this paper, we focus on enumerating collected SVBs empir- ically with initial analysis on their composition manners. The results from this paper will play a dominating role in fueling a coming E-service Economics era.